Intravenous and intraperitoneal paclitaxel with S-1: new hope for patients with pancreatic cancer and peritoneal metastases? - Niesen, Willem; Strobel, Oliver (Translational cancer research, 2016)
Pancreatic ductal adenocarcinoma (PDAC) has a dismal prognosis with a 5-year survival rate still below 7% (1) and is predicted to become the second leading cause of cancer-related mortality within the next two decades (2). Surgical resection in combination with systemic therapy offers the only chance of long-term survival or cure (3). However, at diagnosis only 10-20% of patients have resectable tumors, 30-40% have locally advanced borderline-resectable or unresectable tumors, and the majority of 50-60% of patients present with metastatic disease, frequently with peritoneal metastases (1). Patients with peritoneal metastases have an extremely poor prognosis with survival rates ranging from weeks to several months dependent on the extent of the disease, performance status, and therapy. Peritoneal metastases are frequently associated with severe complications such as intestinal obstruction, massive ascites, and malnutrition. These complications result in a poor performance status and hamper the administration of chemotherapy. Moreover, systemically administered chemotherapeutic drugs may not reach sufficient concentrations in the peritoneal cavity and in peritoneal nodules for effective treatment of peritoneal metastases. More effective treatment strategies for peritoneal metastases are, therefore, one of the most pressing needs in the fight against pancreatic cancer.
Gesehen am 16.11.2017